2000
DOI: 10.1126/science.287.5456.1232
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Ribonucleoprotein Core of the Signal Recognition Particle

Abstract: The signal recognition particle (SRP), a protein-RNA complex conserved in all three kingdoms of life, recognizes and transports specific proteins to cellular membranes for insertion or secretion. We describe here the 1.8 angstrom crystal structure of the universal core of the SRP, revealing protein recognition of a distorted RNA minor groove. Nucleotide analog interference mapping demonstrates the biological importance of observed interactions, and genetic results show that this core is functional in vivo. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
411
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 365 publications
(427 citation statements)
references
References 42 publications
16
411
0
Order By: Relevance
“…Our results suggest that the binding of 4+5S RNA to Ffh not only leads to a structural change of the RNA, as discussed above, but that it also changes the structure of Ffh, although no significant structural change of the M domain fragment is seen in the crystal structure of the M domain-RNA complex (Batey et al+, 2000), compared with the M domain structure of Thermus aquaticus Ffh (Keenan et al+, 1998)+ However, the possibility remains that Ffh-RNA complex formation results in structural changes in parts of the protein that were either not present in the fragment used for crystallization, that is, the NG domain and small parts of the M domain, or that were disordered in the crystal, that is, the finger loop+ In conclusion, the present results suggest that structural details of the tetraloop region of 4+5S RNA, either of the tetraloop itself or of the adjoining stem, influence the structure of SRP such that the binding of FtsY is affected+ This implies that both RNA and Ffh undergo mutual structural adaptation upon association to form SRP+ The presumed structural change in Ffh induced by binding to 4+5S RNA probably extends beyond the M domain, which harbors the binding site for the RNA, as proteolysis data suggest that the structure of both M and NG domains of Ffh changes upon binding 4+5S RNA, indicating an influence of the RNA-binding M domain on the adjacent NG domain, as previously indicated by proteolysis experiments (Zheng & Gierasch, 1997)+ The interaction of Ffh in SRP with FtsY strongly depends on the presence of GTP (Kusters et al+, 1995;Jagath et al+, 2000), and it has been proposed that the conformational state of the G domain in response to the bound nucleotide is signaled to other domains and influences their function (Freymann et al+, 1999)+ It is likely that the modulation of the interdomain communication in Ffh, by ligands such as GTP, 4+5S RNA, or the nascent signal peptide presented by the ribosome, is an important element of the regulation of SRP function+ In this modulation, the SRP RNA appears to have a crucial role beyond that serving as a scaffold for Ffh binding+…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Our results suggest that the binding of 4+5S RNA to Ffh not only leads to a structural change of the RNA, as discussed above, but that it also changes the structure of Ffh, although no significant structural change of the M domain fragment is seen in the crystal structure of the M domain-RNA complex (Batey et al+, 2000), compared with the M domain structure of Thermus aquaticus Ffh (Keenan et al+, 1998)+ However, the possibility remains that Ffh-RNA complex formation results in structural changes in parts of the protein that were either not present in the fragment used for crystallization, that is, the NG domain and small parts of the M domain, or that were disordered in the crystal, that is, the finger loop+ In conclusion, the present results suggest that structural details of the tetraloop region of 4+5S RNA, either of the tetraloop itself or of the adjoining stem, influence the structure of SRP such that the binding of FtsY is affected+ This implies that both RNA and Ffh undergo mutual structural adaptation upon association to form SRP+ The presumed structural change in Ffh induced by binding to 4+5S RNA probably extends beyond the M domain, which harbors the binding site for the RNA, as proteolysis data suggest that the structure of both M and NG domains of Ffh changes upon binding 4+5S RNA, indicating an influence of the RNA-binding M domain on the adjacent NG domain, as previously indicated by proteolysis experiments (Zheng & Gierasch, 1997)+ The interaction of Ffh in SRP with FtsY strongly depends on the presence of GTP (Kusters et al+, 1995;Jagath et al+, 2000), and it has been proposed that the conformational state of the G domain in response to the bound nucleotide is signaled to other domains and influences their function (Freymann et al+, 1999)+ It is likely that the modulation of the interdomain communication in Ffh, by ligands such as GTP, 4+5S RNA, or the nascent signal peptide presented by the ribosome, is an important element of the regulation of SRP function+ In this modulation, the SRP RNA appears to have a crucial role beyond that serving as a scaffold for Ffh binding+…”
Section: Discussionsupporting
confidence: 59%
“…The structure of an RNA fragment comprising domain IV of E. coli 4+5S RNA has been determined by NMR (Schmitz et al+, 1999a(Schmitz et al+, , 1999b)+ Genetic and biochemical analyses indicated that the conserved nucleotides present in the internal loop are important for Ffh binding (Wood et al+, 1992;Lentzen et al+, 1996)+ The crystal structure of the complex of domain IV RNA with an M domain fragment of Ffh shows that the protein interacts with both internal loops and that the structure of loop B in the complex differs from that of the free RNA (Batey et al+, 2000)+…”
Section: Introductionmentioning
confidence: 99%
“…[49][50][51][52] The M domain is mostly helical and contains a highly conserved hydrophobic loop (so-called finger loop), which is disordered in some crystal structures. 47,53 We found that the M domain is inherently flexible and binding of 4.5S RNA to Ffh stabilizes the M domain. 48 Subsequently, in a study that involved the use of fragments of the E. coli protein component of SRP, our lab found evidence that this finger loop itself is detrimental to the stability of the M domain, and proposed that one of the functional requirements FIGURE 1 Protein export to the endoplasmic reticulum (ER) and insertion into the ER membrane in eukaryotes, and to the plasma membrane or the periplasm in E. coli.…”
Section: Srp Structurementioning
confidence: 83%
“…The structural elements found at the N and G interface enable a dynamic communication between these domains. The C-terminal domain of Ffh, called the ''M domain'' because of its high methionine content, comprises the RNAbinding site, 47,48 although some structural studies raise the possibility that the N domain may make contact with the RNA as well. [49][50][51][52] The M domain is mostly helical and contains a highly conserved hydrophobic loop (so-called finger loop), which is disordered in some crystal structures.…”
Section: Srp Structurementioning
confidence: 99%
“…The signal recognition particle (SRP; Walter & Blobel, 1980), like the ribosome, is a cytoplasmic ribonucleoprotein particle (RNP) of ancient evolutionary origin (Poritz et al+, 1990;Bhuiyan et al+, 2000)+ SRP has an intrinsic affinity for ribosomes (Walter et al+, 1981) and its catalytic promotion of the cotranslational mode of protein translocation across membranes is well documented (Walter & Johnson, 1994;Lütcke, 1995)+ In mammals, SRP consists of the highly base-paired 300-nt-long SRP RNA and six proteins: SRP54, SRP19, and the heterodimers SRP68/72 and SRP9/14 (Fig+ 1)+ SRP9/14 associates with the terminal sequences of SRP RNA, forming the enzymatically separable Alu domain of SRP (Gundelfinger et al+, 1983), whereas the other proteins together with the central RNA sequence form the S-domain of SRP+ High resolution crystal structures are now available for a number of SRP components: the NG-and M-domains of SRP54 (Freymann et al+, 1997;Montoya et al+, 1997;Keenan et al+, 1998;Clemons et al+, 1999) and the M-domain in complex with helix 8 of SRP RNA (Batey et al+, 2000) as well as the free helices 6 (Wild et al+, 1999) and 8 (Jovine et al+, 2000) of SRP RNA, free SRP9/14 (Birse et al+, 1997), and, most recently, the Alu domain with SRP9/14 clamping together in its concave beta-sheet the 59 and 39 domains of Alu RNA (Weichenrieder et al+, 2000)+ In electron micrographs the particle appears as a flexible, tri-segmented rod of 60 Å by 260-280 Å with the two domains distinguishable at opposite ends (Andrews et al+, 1985(Andrews et al+, , 1987+ SRP selects ribosomes displaying the N-terminal signal sequence of nascent secretory and membrane proteins that first emerges at the exit pore on the large ribosomal subunit+ The Alu domain of SRP is responsible for retarding the elongation of these proteins once their export signal sequence is bound by the S-domain of SRP and prior to engagement with the translocation machinery in the endoplasmic reticulum+ Considering the apparent length of the particle, it has been pro-posed that the Alu domain might reach the cleft between the two ribosomal subunits where the elongation factors bind (Andrews et al+, 1987;Siegel & Walter, 1988), but the Alu RNP crystal structure does not support the hypothesis that elongation arrest is caused by a mechanism of mimicry-based active competition with elongation factors (Weichenrieder et al+, 2000)+ Knowledge of the preferred orientation and the degree of flexibility of the Alu domain (and the crucial C-termi...…”
Section: Introductionmentioning
confidence: 99%